Identification and Characterization of a Gene stp17 Located on the Linear Plasmid pBSSB1 as an Enhanced Gene of Growth and Motility in Salmonella enterica Serovar Typhi - Zhang, Haifang; Zhu, Yunxia; Xie, Xiaofang; Wang, Min; Du, Hong; Xu, Shungao; Zhang, Ying; Gong, Mingyu; Ni, Bin; Xu, Huaxi; Huang, Xinxiang (Frontiers in Cellular and Infection Microbiology, 2016)
The linear plasmid pBSSB1 mediates the flagellar phase variation in H:z66 positive Salmonella enterica serovar Typhi (S. Typhi). The gene named stp17 (S. Typhi plasmid number 17 gene) is located on pBSSB1 and encodes the protein STP17. The expression pattern at the protein-level and function of STP17 remains unknown. In this study, the recombinant protein STP17His6 was expressed, successfully purified and used to prepare the polyclonal anti-STP17 antibody. We detected protein-level expression of stp17 in S. Typhi and further investigated the protein expression characteristics of stp17 in different growth phases by western blot analysis. The effects of STP17 on bacterial growth and motility were analyzed. In addition, the structure of STP17 was predicted on line and the active site of STP17 was identified by site-directed mutagenesis. The results showed that STP17 was expressed stably in the wild type strain of S. Typhi. STP17 expression at the protein level peaks when cultures reach an OD600 value of 1.2. The growth rate and motility of the Δstp17 strain were significantly decreased compared with the wild type strain (P<0.05) and this phenotype was restored in the stp17 complementary strain. Moreover, the growth rate and motility of the stp17 over-expression strain was greater than the wild type strain. STP17 contains nine Helix segments, six Stand segments and some Coil segments in the secondary structural level. The top-ranked 3-D structure of STP17 predicted by I-TASSER contains a putative ATPase domain and the amino acid residues of GLY16, GLY19, LYS20, ASN133, LYS157 and LYS158 may be the active site residues of STP17. Finally, STP17 was able to catalyze the ATP to ADP reaction, suggesting that STP17 may be an ATPase. To our knowledge, this is the first report describing the protein expression characteristics of STP17 in S. Typhi, showing that STP17 promotes bacterial growth and motility, which may be associated with its potential ATPase activity.